Comparison of herd composition and infrastructure facilities in specialized dairy farms between north and south Gujarat (Indian Journal of Animal Production and Management, 2024)
The present investigation was carried out to compare herd composition (buffaloes, cows, heifers, calves,  breeding bull, total herd strength) and infrastructure facilities (assets and implements) of specialized dairy  farms in north (n=10) and south (n=10) semi-arid to arid and medium to high rainfall agro-climatic zones  respectively. In northern region higher mean average of cross-breed cattle (82.20 vs. 23.25, p=0.01)  compared to southern region. Opposite to this in southern region higher mean average of buffalo (85.00  vs. 3.77, p=0.00) compared to northern region. Whereas in southern region slightly higher mean average  of total herd strength (111.70 vs. 86.60, p=0.11) compared to northern region. The facility of infrastructure in  both region possessed similar proportion of average adult animal shed, individual calf shed, pregnant animal  shed, sick animal shed. Store-dutch barn, milking parlour, feed factory, labour house, milk storage room,  staff office, tractor, hydraulic trailer, mannual as well as electric chaff cutter, shredder, water pipe router,  dung scraper, automatic grooming brush, bulk milk cooler, milking parlour, deep freezer, automatic ghee  maker and milk packaging machine. However, Northern region had higher proportion of milking machine  (80% vs. 20%, p=0.00) as compare to southern region. Present study indicated that herd composition  differed between two regions might be attributed to climatic difference including moisture and rainfall  pattern along with marketing pattern.
Keywords: Cross breed; Herd composition; Infrastructure facilities; Milking machine; Specialized dairy farm